TRANSITION AND CONTINUITY OF n-LINEAR AND POLYNOMICAL TRANSFORMERS - Маслюченко, Володимир Кирилович; Нестеренко, Василь Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is proved that the transitivity for n-linear and polynomial transformers is equivalent to continuity.